'Omic' technologies as a helpful tool in radioecological research. (September 2018) - Volkova, Polina Yu.; Geras'kin, Stanislav A.
Abstract: This article presents a brief review of the modern 'omic' technologies, namely genomics, epigenomics, transcriptomics, proteomics, and metabolomics, as well as the examples of their possible use in radioecology. For each technology, a short description of advances, limitations, and instrumental applications is given. In addition, the review contains examples of successful use of 'omic' technologies in the assessment of biological effects of pollutants in the field conditions. Highlights: 'Omic' technologies are appropriate tools for radioecological research. Systems biology methods can facilitate field radioecological studies. Fast revealing of mode of action and adverse outcome pathways.